Drying Medicinal Plants With The Storage Of Antioxidant Properties - Sultanova Sh.A., Safarov J.E., Raxmanova T.T. (International Journal of Advanced Science and Technology, 2020)
Studies on the residual amount of antioxidants were performed on rose hips and hawthorn. These objects were dried by various drying methods. Results on the detection of antioxidants by creeping dried plants in a facility that was developed by the authors. The content of phenolic compounds in the studied plants was carried out spectrophotometrically. Extracts were prepared from dried plants. The total amount and content of DPPH radical removal were determined.